Spectrophotometric and Derivative Spectrophotometric Determination of Iron(III) with 3-Hydroxy-2-Picolinamide - Gaur, Aprajita; Bhajan Singh, Har; Lal Sharma, Rattan; Kumar Singh, Vinay (Asian Journal of Chemistry, 2010)
3-Hydroxy-2-picolinamide gives a colour reaction with iron(III) which has been developed into a method for spectrophotometric determination of iron(III) in both derivative as well as normal modes. Molar absorptivity and Sandell's sensitivity of the complex at its λmax (475 nm) have been found to be 2.244 x 103l mol–1cm–1 and 0.0248 μg cm–2 respectively. Beer's law is followed from 0.2 mM to 0.8 mM of iron(III). Interference due to the presence of a number of cations and anions has been studied and the method successfully applied to determine iron contents of iron formulations and a cement sample.